(untitled) (Nepal Journal of Neuroscience, 2026)
Objective: Ventriculo-subgaleal shunt is an internal CSF diversion technique, communicating the dilated ventricles to the subgaleal pouch developed in the scalp. In infants due to infection or hemorrhage in the brain, hydrocephalus can develop due to multifactorial causes. These infants, predominantly present with failure to thrive. This leads to high rates of patient and procedure related complications following ventriculo-peritoneal shunt, with an overall increase in hospitalization and shunt failure. ventriculo-subgaleal shunt is a less invasive procedure and provides sufficient time for the child to improve their nutritional status. We aim to study the effectiveness of ventriculo-subgaleal shunts in infants with post-hemorrhagic/ post infectious hydrocephalus. Methodology: The infants who underwent ventriculo-subgaleal shunt between January 2021 and June 2023 at Christian Medical College, Vellore were retrospectively analyzed. Results: Four infants were managed with VSG shunt as a temporary means of CSF diversion. All these four infants weighed less than 2500 grams and presented with progressive head growth and failure to thrive. Three of them were female and the mean age was 3.5 months. Three infants were pre-term in our series. Post infectious hydrocephalus was the most common etiology found in our series. All the infants were followed up for 2 months at which time they improved symptomatically. All the infants underwent ventriculo-peritoneal shunt as definitive procedure later. Conclusion: Ventriculo-subgaleal shunt is an easy and safe procedure. It is suited for infants who are preterm or low birth weight, to avoid the morbidity and failure rates of regular ventriculo-peritoneal shunt.